The self-determination theory applied in the analysis of motivation and academic performance of accounting students in a brazilian public university - Borges, Marina Salgado (2017)
The aim of this study was analyzing the relations between academic performance and motivation of Accounting students in a Brazilian public university based on Self-determination Theory. Methodologically, in order to reach that, structured questionnaires were applied in classrooms with the Brazilian version of the Academic Motivation Scale (AMS), in a sample of 316 students enrolled from second to tenth periods of that course, equivalent to 37.2% of the total number of students. Data were analyzed using descriptive statistics, exploratory factor analysis (AFE) and multiple linear regression analysis with Ordinary Least Squares (OLS). The regression analyzes indicated a significant relationship between motivation and academic performance. The factors related to intrinsic motivation and extrinsic motivation by identified regulation are positively correlated with academic performance of students. On the other hand, the introjected for regulation extrinsic motivation factor is negatively correlated with student’s academic performance coefficient (CRA). Based on the sample analyzed, the results showed that the relationship between motivation and CRA of the student depends on the type of motivation that is present in each one.